The ICT Literacy Level of EFL Students at IAIN Syekh Nurjati Cirebon - Edy Waloyo; Rudi Hartono; Sri Wahyuni; Henrikus Joko Yulianto (International Conference on Science, Education, and Technology, 2022)
Abstrak. Pandemic era effects to the teaching and learning English process. It also forces students to use laptop and gadget in joining the class and completing the assignments. Information and Communication Technology Literacy (ICTL) is essential for EFL students in facilitating their daily activities in studies. The students’ engagement with technology can illustrate their ICTL level. This research aims to explain the ICTL level of EFL students at IAIN Syekh Nurjati Cirebon. The method of analysis for this purpose is a descriptive survey analysis. The participants of this study are 6th semester students. The data is collected through questionnaires. The data will be collected and analyzed through the theory proposed by ICTL Panel 2007. The data was analyzed in percentages, frequency counts, and make conclusions. The finding showed that the level of ICTL of EFL students at IAIN Syekh Nurjati was high cognitively and practically. It can be seen that the means score of cognitive proficiency was 80.82%. Moreover, the data of students’ practical proficiency was 75.62%. Based on the data above, it can be said that the students are ICT literate and have high competency using technology.Key words: ICTL level, EFL students, descriptive survey, high competency